2014
DOI: 10.2478/s13382-014-0275-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead, cadmium and mercury among children from urban, industrial and rural areas of Fez Boulemane Region (Morocco): Relevant factors and early renal effects

Abstract: Objectives: To describe blood lead (Pb-B), cadmium (Cd-B) and mercury (Hg-B) levels in children living in urban, industrial and rural areas in Fez city (north of Morocco) and to identify the determinants and some renal effects of exposure. Material and Methods: The study was conducted from June 2007 to January 2008 in 209 school children (113 girls, 96 boys), aged 6-12 years, from urban, industrial and rural areas in Fez city. Interview and questionnaires data were obtained. Blood and urinary samples were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…One particular focus of this study was the difference of area of residence because cadmium, lead, and mercury are known to be vehicular traffic-related heavy metals [37,38]. Our results indicated that urban populations showed a stronger link between blood heavy metal levels and 10-year ASCVD risk score, whereas rural populations showed no significant associations mainly among men.…”
Section: Discussionmentioning
confidence: 70%
“…One particular focus of this study was the difference of area of residence because cadmium, lead, and mercury are known to be vehicular traffic-related heavy metals [37,38]. Our results indicated that urban populations showed a stronger link between blood heavy metal levels and 10-year ASCVD risk score, whereas rural populations showed no significant associations mainly among men.…”
Section: Discussionmentioning
confidence: 70%
“…By contrast, the toxic Pb and Hg were found at statistically higher levels in the serum of industrial site residents ( Figure 11 ), with the lowest concentrations of most metals observed in the samples of rural site residents, further implying the possible contribution of the local air quality on serum’s concentrations. In other studies, Pb blood levels were elevated in urban areas citizens compared to those of industrial and rural, while Hg was higher in the industrial citizens’ samples [ 127 ]. Significant associations between airborne trace elements and the corresponding serum levels were also found in a study conducted in China, with those who lived in urban sites, under elevated Pb and Cd emissions, presenting increased levels in their serum [ 79 ].…”
Section: Resultsmentioning
confidence: 97%
“…Four (4) studies did not measure the exposure at an individual level, these studies measured proximity to a high exposure source (Lagutina et al, 1979, Ignatova et al, 1996, D’Andrea and Reddy, 2014). Four (4) studies reported multiple exposures, such as lead and cadmium (Chan et al, 2012, Pels et al, 1998), or cadmium and mercury (Laamech et al, 2014, de Burbure et al, 2006). Outcome measure definitions were generally consistent.…”
Section: Resultsmentioning
confidence: 99%
“…A case-control study from the United States found no difference in creatinine clearance in children with lead poisoning (exposure levels 100–471 μg/dl) compared to sibling controls (Moel et al, 1985). A cross-sectional study of 196 children in Morocco found no significant correlations between blood lead and urine RBP and albumin levels (Laamech et al, 2014). A cross-sectional study of 246 children in Pakistan also found no significant difference in serum urea or serum creatinine levels between exposed (children of lead-exposed industrial workers) and unexposed (children of non-exposed workers) groups (Khan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%